2017
DOI: 10.17116/hirurgia2017419-23
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the intra-operative neuromonitoring data and emg-characteristics of post-operative motor deficit in patients with spinal deformities

Abstract: We suggested the scale of intra-operative pyramidal disorders severity that is satisfactorily correlated with functional surgical outcomes which are reflected in the dynamics of particular and integral characteristics of voluntary and evoked bioelectrical activity of the lower limb muscles. This fact makes possible to use safely the above-mentioned protocol for IONM, to predict postoperative motor disorders and to formulate reasonably the recommendations for postoperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…However, in the absence of clinical signs of neurological disorders, instrumental research methods make it possible to identify more pronounced deviations of EMG parameters in the patients who have undergone negative intraoperative events, than in those after a smooth course of surgery. [ 11 , 12 ]. This condition has been defined as subclinical sensorimotor deficit [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the absence of clinical signs of neurological disorders, instrumental research methods make it possible to identify more pronounced deviations of EMG parameters in the patients who have undergone negative intraoperative events, than in those after a smooth course of surgery. [ 11 , 12 ]. This condition has been defined as subclinical sensorimotor deficit [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors interpret these alterations as false positive responses of the pyramidal tract of the spinal cord [ 9 ], however, there is no unanimous opinion on this issue [ 7 , 10 ]. The results of our studies have shown that even in the absence of postoperative neurological deficit, adverse intraoperative events accompanied by negative changes in the MEP lead to a decrease in neurophysiological sensorimotor parameters [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%